Exchange rates and export growth in Asian economies - Mohamad, Saadiah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
This paper discusses the impact of exchange rates on the export performance of selected Southeast Asian economies, namely, Indonesia, Malaysia, Singapore and Thailand. We construct an empirical model to account for the role of the real exchange rate and other economic fundamentals such as macroeconomic stability, terms of trade, capital goods investment, external demand and human capital. The study makes use of a panel data and estimates an export equation using a fixed effect model. The findings in this study strongly corroborate results from the theoretical framework that exchange rate misalignment and exchange rate variability have significant impacts on export performance. The study also finds evidence that the export growth path or these selected economies are dependent on global demand conditions, especially demand from OECD countries.